The Intersection between Constitution, Human Rights and the Environment: The French Charter for the Environment and the New Ex Post Constitutional Control in France. (June 2014) - Marrani, David
There is a lot to be said about how environmental issues are reshaping the way we are living in the twenty-first century. Not only are those issues affecting the human race, but they are also affecting legal orders, sometimes even in their most conservative 'parts'. The Charter for the Environment was integrated in the French Fifth Republic Constitution in 2005. It became the legal basis of many unforeseen changes, particularly the important recognition of its value by the 'public law' courts. Environmental rights seem to have become human rights after the 2008 landmark decision of the French Constitutional Council on the constitutionality of the statute on GMOs. In that decision, the Council reaffirmed the constitutional value of every right and duty defined in the Charter. The impact of this statement has recently been amplified with the introduction by the 2008 constitutional amendment of an ex post constitutional control. It is, therefore, time to consider whether the rights declared in the Charter are becoming 'true' constitutional rights.